Less severe clinical symptoms of Norwalk virus 8fIIb inoculum compared to its precursor 8fIIa from human challenge studies. Issue 6 (30th October 2020) - Liu, Pengbo; Rahman, Mumu; Leon, Juan; Moe, Christine
Abstract: Noroviruses (NoV) are a leading cause of epidemic gastroenteritis. Human challenge studies have been used to examine the infectivity, pathogenicity, and host immune response to NoV as well as vaccine efficacy. The goal of this study was to conduct a meta‐analysis of data from five previously completed human challenge trials and compare the response to the secondary NV inoculum (8fIIb) to its precursor (8fIIa). We investigated a total of 158 subjects: 76 subjects were experimentally challenged with NV inoculum 8fIIa, and 82 subjects were challenged with 8fIIb. We compared demographic characteristics, infection, illness, mean severity score, blood types, and duration of viral shedding between the two groups of subjects. There were no statistically significant differences in overall infection and illness rates between subjects inoculated with 8fIIa and 8fIIb. However, individuals challenged with 8fIIa had significantly higher severity scores (5.05 vs. 3.22, p = .008) compared with those challenged with 8fIIb. We also observed that infection with 8fIIb was associated with significantly longer duration of viral shedding compared with 8fIIa (11.0 days vs. 5.0 days, p = .0005). These results have serious implications for the development of new NoV inocula for human challenge studies to test candidate vaccine efficacy—where illness severity and duration of viral shedding are important outcomes.